Electrode mixture for battery and nonaqueous electrolyte secondary battery
Patent Information
- Application Number
- CN202280015625.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-02-26
- Filing Date
- 2022-02-01
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2042-02-01
AI Technical Summary
[0013]根据本发明的电池用电极合剂,能够改善电池的循环特性。在使用了本发明的电极合剂的非水电解质二次电池中,活性物质与电解液的副反应被抑制,其结果,能得到优异的循环特性。
Smart Images

Figure CN116897441B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an electrode mixture for batteries and a non-aqueous electrolyte secondary battery having an electrode constructed using the electrode mixture. Background Technology
[0002] Electrodes in non-aqueous electrolyte secondary batteries such as lithium-ion batteries generally include an electrode layer containing an active material capable of absorbing and releasing lithium ions. The electrode electrode layer significantly influences battery performance, including input / output characteristics, capacity, and charge / discharge cycle characteristics; therefore, much research has been conducted on the electrode electrodes constituting the layer. For example, Patent Document 1 discloses a lithium secondary battery comprising a positive electrode with a silane coupling agent dispersed in the electrode layer. This silane coupling agent has organic reactive groups composed of epoxy and / or amino groups, and inorganic reactive groups composed of methoxy and / or ethoxy groups. Patent Document 1 describes how dispersing the silane coupling agent in the positive electrode improves the wettability of the positive electrode with the electrolyte at low temperatures.
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent Document 1: Japanese Patent Application Publication No. 2002-319405 Summary of the Invention
[0006] The problem the invention aims to solve
[0007] However, it is known that during repeated charge-discharge cycles, the capacity gradually decreases due to side reactions between the active material and the electrolyte. Therefore, suppressing these side reactions, inhibiting the capacity reduction accompanying charge-discharge cycles, and improving the battery's cycle characteristics are important issues. It should be noted that the technology in Patent Document 1 does not consider the improvement of cycle characteristics.
[0008] The purpose of this invention is to provide an electrode compound for batteries that can improve the cycle characteristics of batteries.
[0009] Solution for solving the problem
[0010] As one aspect of the present invention, the battery electrode mixture is characterized in that it comprises an active material capable of absorbing and releasing lithium, and the electrode mixture further comprises an ionic compound bound to the surface of the active material, the ionic compound comprising: a binding site with the active material, an organic cation, and a counterion of the organic cation.
[0011] As one aspect of the present invention, a non-aqueous electrolyte secondary battery comprises: a positive electrode, a negative electrode, and a non-aqueous electrolyte, wherein at least one of the electrode mixture layers of the positive electrode and the negative electrode is composed of the aforementioned electrode mixture.
[0012] The effects of the invention
[0013] The electrode compound for batteries according to the present invention can improve the cycle characteristics of batteries. In non-aqueous electrolyte secondary batteries using the electrode compound of the present invention, side reactions between the active material and the electrolyte are suppressed, resulting in excellent cycle characteristics. Attached Figure Description
[0014] Figure 1 This is a cross-sectional view of a non-aqueous electrolyte secondary battery as an example of an implementation method.
[0015] Figure 2 This is a schematic diagram showing the state of the surface of an active material as an example of an implementation method. Detailed Implementation
[0016] As mentioned above, suppressing side reactions between the active material and the electrolyte and improving the cycle characteristics of the battery are important issues. To address this issue, the inventors conducted in-depth research and discovered that by adding ionic compounds bound to the surface of the active material, the capacity retention after charge-discharge cycles is improved, and the cycle characteristics are specifically improved. It is believed that the electrolyte acts as a buffer layer for the ionic compounds containing organic cations bound to the surface of the active material, without directly contacting the surface of the active material. Furthermore, it is believed that this buffer layer suppresses side reactions between the active material and the electrolyte and improves cycle characteristics.
[0017] Furthermore, the improvement in cycle characteristics is more significant when the content of ionic compounds relative to the active material is 0.2–1.8% by mass. The electrode compound of this invention can be applied to the negative electrode, but it is more effective for the positive electrode.
[0018] Hereinafter, an example of an embodiment of the electrode mixture for batteries and the non-aqueous electrolyte secondary battery of the present invention will be described in detail with reference to the accompanying drawings. It should be noted that the various embodiments and modifications described below are initially envisioned to be selectively combined.
[0019] The following example illustrates a cylindrical battery in which a wound electrode 14 is housed within a bottomed cylindrical outer casing 16. However, the outer casing is not limited to a cylindrical shape; for example, it can be a square casing (square battery), a coin-shaped casing (coin-shaped battery), or an outer casing made of a laminate containing a metal layer and a resin layer (laminated battery). Furthermore, the electrode is not limited to a wound type; it can also be a stacked electrode, consisting of multiple positive electrodes and multiple negative electrodes alternately stacked with separators. The electrode mixture for batteries of the present invention is also applicable to aqueous electrolyte secondary batteries using an aqueous electrolyte, but it is particularly effective in non-aqueous electrolyte secondary batteries using a non-aqueous electrolyte.
[0020] Figure 1 This is a cross-sectional view of a non-aqueous electrolyte secondary battery 10, as an example of an embodiment. (See diagram below.) Figure 1 As shown, the non-aqueous electrolyte secondary battery 10 includes: a wound electrode body 14, a non-aqueous electrolyte, and a housing 16 for housing the electrode body 14 and the non-aqueous electrolyte. The electrode body 14 has: a positive electrode 11, a negative electrode 12, and a separator 13, and has a wound structure in which the positive electrode 11 and the negative electrode 12 are wound into a spiral shape with the separator 13 in between. The housing 16 is a bottomed cylindrical metal container with an opening on one axial side, and the opening of the housing 16 is blocked by a sealing body 17. Hereinafter, for ease of explanation, the side with the sealing body 17 of the battery is referred to as the upper part, and the bottom side of the housing 16 is referred to as the lower part.
[0021] Non-aqueous electrolytes comprise: a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. Examples of non-aqueous solvents include esters, ethers, nitriles, amides, and mixtures of two or more thereof. The non-aqueous solvent may also contain halogen-substituted derivatives in which at least a portion of the hydrogen atoms of these solvents are replaced by halogen atoms such as fluorine. Examples of non-aqueous solvents include ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), and mixtures thereof. Examples of electrolyte salts include lithium salts such as LiPF6.
[0022] The positive electrode 11, negative electrode 12, and spacer 13 constituting the electrode body 14 are all strip-shaped elongated bodies, and are alternately stacked radially along the electrode body 14 by spiral winding. The negative electrode 12 is formed to be one size larger than the positive electrode 11 to prevent lithium deposition. That is, the negative electrode 12 is formed to be longer than the positive electrode 11 in both the length and width directions (short side direction). The spacer 13 is formed to be at least one size larger than the positive electrode 11, for example, two sheets are arranged to clamp the positive electrode 11. The electrode body 14 has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.
[0023] Insulating plates 18 and 19 are respectively disposed above and below the electrode body 14. Figure 1 In the example shown, the positive lead 20 extends towards the sealing body 17 through the through hole in the insulating plate 18, and the negative lead 21 extends towards the bottom of the outer casing 16 through the outer side of the insulating plate 19. The positive lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the top plate, i.e., the cover 27, of the sealing body 17, which is electrically connected to the internal terminal plate 23, becomes the positive terminal. The negative lead 21 is connected to the inner bottom surface of the outer casing 16 by welding or the like, and the outer casing 16 becomes the negative terminal.
[0024] A gasket 28 is provided between the outer casing 16 and the sealing body 17 to ensure the airtightness of the battery interior. A groove 22 is formed on the outer casing 16, a portion of which protrudes inward to support the sealing body 17. The groove 22 is preferably formed in a ring shape along the circumference of the outer casing 16, and its upper surface supports the sealing body 17. The sealing body 17 is fixed to the upper part of the outer casing 16 by the groove 22 and the open end of the outer casing 16 that fastens the sealing body 17.
[0025] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26, and a cover 27 are stacked sequentially from the electrode body 14 side. Each component constituting the sealing body 17 has, for example, a circular or annular shape, and all components except the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective central portions, and the insulating member 25 is sandwiched between their respective peripheral portions. When the internal pressure of the battery rises due to abnormal heating, the lower valve body 24 deforms and breaks by pressing the upper valve body 26 towards the cover 27, thereby blocking the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 breaks, and gas is discharged from the opening of the cover 27.
[0026] The following describes in detail the positive electrode 11, negative electrode 12, separator 13 constituting the electrode body 14, and especially the electrode mixture constituting the mixture layer of the positive electrode 11 and negative electrode 12.
[0027] [Electrode Mixture]
[0028] As one example of an embodiment, the electrode compound comprises: an active material capable of absorbing and releasing lithium ions and an ionic compound bound to the surface of the active material. The ionic compound contains: a binding site with the active material, an organic cation, and an anti-cation of the organic cation. Even in very small amounts, the ionic compound has the effect of suppressing side reactions between the active material and the electrolyte, contributing to improved battery cycle characteristics; however, the content of the ionic compound relative to the mass of the active material is preferably 0.2% by mass or more. Furthermore, the upper limit of the content of the ionic compound is preferably 1.8% by mass.
[0029] The electrode mixture used as an example of an embodiment can also be applied to the negative electrode 12, but it is particularly effective in the positive electrode 11. Hereinafter, the mixture layer of the positive electrode 11 is described using the electrode mixture used as an example of an embodiment.
[0030] [positive electrode]
[0031] The positive electrode 11 includes a positive electrode core 30 and a positive electrode additive layer 31 disposed on the surface of the positive electrode core 30. The positive electrode core 30 can be made of a foil of a metal that is stable within the potential range of the positive electrode 11, such as aluminum or an aluminum alloy, or a thin film of the metal disposed on its surface. The positive electrode additive layer 31 is preferably disposed on both sides of the positive electrode core 30. The positive electrode 11 can be manufactured, for example, by coating a slurry of a positive electrode additive onto the positive electrode core 30, drying the coating, and then compressing it to form the positive electrode additive layer 31 on both sides of the positive electrode core 30.
[0032] The positive electrode mixture layer 31 comprises: a positive electrode active material and the aforementioned ionic compound. The positive electrode mixture layer 31 preferably also comprises a binder and a conductive agent. The positive electrode mixture layer 31 is formed, for example, by coating a slurry containing a positive electrode active material, a binder, a conductive agent, and an ionic compound onto the positive electrode core 30. The dispersion medium of the positive electrode mixture slurry is not particularly limited as long as it can disperse the positive electrode mixture; for example, N-methyl-2-pyrrolidone (NMP) can be used. The ionic compound can be mixed with the positive electrode active material before slurry formation, or it can be mixed with the positive electrode active material by adding it to the slurry in which the positive electrode active material is dispersed.
[0033] Examples of binders included in the positive electrode binder layer 31 (positive electrode binder) include fluoropolymers such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide, acrylic resins, and polyolefins. These resins can be used in combination with cellulose derivatives such as carboxymethyl cellulose (CMC) or its salts, and polyethylene oxide (PEO). The binder content relative to the mass of the positive electrode binder layer 31 is, for example, 0.5 to 2.0% by mass.
[0034] The conductive agent contained in the positive electrode additive layer 31 forms a good conductive path in the additive layer, which helps to reduce the resistance of the additive layer. Examples of conductive agents include particulate conductive agents such as carbon black, acetylene black, Ketjen black, and graphite; fibrous conductive agents such as carbon nanotubes (CNTs), vapor-grown carbon fibers (VGCF), electric field-spun carbon fibers, polyacrylonitrile (PAN) based carbon fibers, pitch-based carbon fibers, and graphene. The content of the conductive material relative to the mass of the positive electrode additive layer 31 is, for example, 0.5 to 2.0% by mass.
[0035] The preferred positive electrode active material is a lithium-containing transition metal composite oxide. Examples of elements contained in this lithium-containing transition metal composite oxide include Ni, Co, Mn, Na, K, Mg, Ca, Sr, Ba, Sc, Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Ge, Sn, Pb, Sc, Ti, Si, V, Cr, Fe, Cu, Zn, Ru, Rh, Re, Pd, Ir, Ag, Bi, Sb, B, Al, Ga, In, P, Zr, Hf, Nb, Mo, and W. Preferably, it contains at least one of Ni, Co, and Mn.
[0036] A preferred example of a lithium-containing transition metal composite oxide is one with a layered rock salt-type crystal structure and composed of the general formula LiNi. x M 1-x O2 (where M is at least one selected from the group consisting of Al, Mn, and Co, and 0.3 ≤ x < 1.0) represents a composite oxide. Composite oxides with high Ni content are effective for increasing battery capacity. The composite oxide represented by the above general formula has good compatibility with layered silicate compounds. By using this composite oxide, high battery capacity can be achieved, and the diffusion of lithium ions in the positive electrode binder layer 31 can be improved more effectively.
[0037] The positive electrode active material uses a lithium-containing transition metal composite oxide represented by the above general formula as its main component. Here, the main component refers to the component with the highest mass ratio among the constituent components of the composite oxide. In the positive electrode additive layer 31, composite oxides other than those represented by the above general formula can be used as the positive electrode active material, but the content of the above composite oxides is preferably 50% by mass or more, and can actually be 100% by mass. It should be noted that the composition of the composite oxide can be determined using an ICP emission spectrometer (Thermo Fisher Scientific iCAP6300).
[0038] Lithium-containing transition metal composite oxides are, for example, secondary particles formed by the aggregation of multiple primary particles. An example of the median particle size (D50) on a volume basis for lithium-containing transition metal composite oxides is 1–20 μm or 2–15 μm. D50 is the particle size at which the cumulative volume value in the particle size distribution determined by laser diffraction scattering is 50%. The BET specific surface area of the composite oxide is, for example, 1.0–4.0 mm². 2 / g. If the BET specific surface area is within this range, it is easy to achieve both high durability and high capacity. The BET specific surface area is determined according to the BET method (nitrogen adsorption method) described in JIS R1626.
[0039] As described above, the positive electrode compound layer 31 contains an ionic compound. The ionic compound is a compound containing a binding site for the active material, an organic cation, and an anti-anion of the organic cation, which chemically binds to the particle surface of the positive electrode active material through the binding site. The content of the ionic compound relative to the mass of the positive electrode active material is preferably 0.2% by mass or more, more preferably 0.3% by mass or more, and particularly preferably 0.5% by mass or more. The upper limit of the content of the ionic compound is preferably 1.8% by mass, more preferably 1.7% by mass, and particularly preferably 1.5% by mass.
[0040] Figure 2 This is a schematic diagram illustrating the state of the particle surface of the positive electrode active material. For example... Figure 2 As shown, by binding ionic compounds to the surface of the positive electrode active material particles, it is believed that the organic cation portion of the ionic compound acts as a buffer layer, suppressing side reactions between the active material and the electrolyte. Therefore, even with repeated charge-discharge cycles, the capacity is unlikely to decrease, resulting in excellent cycle characteristics. In particular, the improvement in cycle characteristics is significant when the content of the ionic compound relative to the positive electrode active material is 0.2–1.8% by mass. An example of a preferred range for the content of the ionic compound relative to the mass of the positive electrode active material is 0.2–1.8% by mass, or 0.3–1.7% by mass, or 0.5–1.5% by mass.
[0041] The binding site of the ionic compound to the positive electrode active material is, for example, connected to an organic cation via a hydrocarbon chain. Functional groups such as hydroxyl groups are present on the surface of the positive electrode active material. Therefore, the functional groups of the ionic compound react with the functional groups on the surface of the positive electrode active material to form a chemical bond at the binding site. This functional group of the ionic compound only needs to be reactive with the functional groups of the positive electrode active material; preferred examples include hydrolyzable silyl groups, epoxy groups, and carboxyl groups. Hydrolyzable silyl groups are preferred. That is, the binding site of the ionic compound is preferably derived from a hydrolyzable silyl group. In this case, it is believed that a Si-containing layer can be formed on the surface of the positive electrode active material, improving the protective function of the active material surface.
[0042] The aforementioned hydrolyzable silanes are, for example, alkoxysilanes. Figure 2 The diagram illustrates a binding site derived from a trimethoxysilyl group. It should be noted that the alkoxysilyl group is not limited to methoxysilyl groups and can also be ethoxysilyl groups, etc. The functional groups of the ionic compound may not all be bound to the surface of the positive electrode active material; therefore, the positive electrode binder layer 31 may also contain ionic compounds that are not bound to the surface of the positive electrode active material.
[0043] The organic cation of the ionic compound is acceptable as long as it is electrochemically stable in the positive electrode mixture layer 31 and does not impede stability in the positive electrode mixture slurry used to form the positive electrode mixture layer 31. The organic cation may include, for example, at least one selected from the group consisting of ammonium cations, imidazolium cations, piperidinium cations, pyridinium cations, pyrrolidineonium cations, morpholinium cations, sulfonium cations, and phosphonium cations. Among these, imidazolium cations, ammonium cations, phosphonium cations, piperidinium cations, pyridinium cations, and pyrrolidineonium cations are preferred.
[0044] In this embodiment, Figure 2 The molecular structure of the ionic compound shown is represented by part A as an organic cation and part B as a binding site. Figure 2 In this context, the organic cation is a 1-methylimidazolium cation. It should be noted that the organic cation is not limited to this; it can also be a 1-alkylimidazolium cation, a 1,2-alkylimidazolium cation, etc. (the alkyl group being, for example, an alkyl group having 10 or fewer carbon atoms), or any organic cation other than imidazolium. Furthermore, the organic cation is connected to the bonding site via a hydrocarbon chain. An example of this hydrocarbon chain is a straight-chain hydrocarbon having 10 or fewer carbon atoms, or 5 or fewer carbon atoms.
[0045] The anions of ionic compounds, like the cations, can be electrochemically stable in the positive electrode mixture layer 31 and not hindered in their stability in the positive electrode mixture slurry used to form the positive electrode mixture layer 31. Anions may include, for example, those selected from PF6. - BF4 - N(SO2CF3)2 - N(SO2F)2 - PO2F2 - At least one of the following groups: bis(oxalato)borate anion and difluoro(oxalato)borate anion. PF6 is preferred. - BF4 - N(SO2CF3)2 - PO2F2 - It should be noted that when using an ionic compound in the negative electrode 12 made from an aqueous slurry, an imide-based anion is preferred as the anion.
[0046] In ionic compounds, for example, the content of the binding site with the positive electrode active material is 0.5% by mass or less relative to the total mass of the positive electrode active material and the ionic compound. When the binding site originates from a silicon (Si) functional group such as a hydrolyzable silane, the Si content is preferably 0.03 to 0.25% by mass relative to the total mass of the positive electrode active material and the ionic compound. The Si content can be determined by inductively coupled plasma mass spectrometry (ICP-MS). If the Si content is within this range, the ionic compound exhibits good reactivity on the surface of the positive electrode active material and can more effectively suppress side reactions between the active material and the electrolyte.
[0047] Ionic compounds can be bonded to the surface of the positive electrode active material by reacting hydrolyzable silane functional groups with functional groups on the surface of the positive electrode active material, for example, by mixing with powdered positive electrode active material or by mixing with a positive electrode slurry in which the positive electrode active material is dispersed. This reaction can be carried out at room temperature. Alternatively, ionic compounds can be synthesized, for example, by the methods described in the examples below.
[0048] [negative electrode]
[0049] The negative electrode 12 comprises a negative electrode core 40 and a negative electrode binder layer 41 disposed on the surface of the negative electrode core 40. The negative electrode core 40 may be a foil of a metal stable within the potential range of the negative electrode 12, such as copper, or a thin film of the metal disposed on its surface. The negative electrode binder layer 41 is preferably disposed on both sides of the negative electrode core 40. The negative electrode 12 can be manufactured, for example, by coating a slurry of a negative electrode binder onto the negative electrode core 40, drying the coating, and then compressing it to form the negative electrode binder layer 41 on both sides of the negative electrode core 40. The negative electrode binder layer 41 (negative electrode binder) comprises a negative electrode active material and a binder. The negative electrode binder layer 41 may also contain the aforementioned ionic compound bonded to the surface of the negative electrode active material.
[0050] In the negative electrode additive layer 41, the negative electrode active material includes, for example, a carbon-based active material that reversibly absorbs, stores, and releases lithium ions. Preferred carbon-based active materials include natural graphite such as flake graphite, block graphite, and amorphous graphite, as well as artificial graphite such as blocky graphite (MAG) and graphitized mesophase carbon microspheres (MCMB). Alternatively, the negative electrode active material may be a Si-based active material composed of at least one of Si and Si-containing compounds, or a combination of carbon-based and Si-based active materials may be used.
[0051] The binder contained in the negative electrode binder layer 41 is similar to that in the positive electrode 11; it can be fluoropolymers, PAN, polyimide, acrylic resins, polyolefins, etc., but styrene-butadiene rubber (SBR) is preferred. Furthermore, the negative electrode binder layer 41 preferably contains CMC or its salts, polyacrylic acid (PAA) or its salts, polyvinyl alcohol (PVA), etc. It is preferred that SBR is used in combination with CMC or its salts, and PAA or its salts. It should be noted that the negative electrode binder layer 41 may also contain a conductive agent.
[0052] [Separator]
[0053] The separator 13 is a porous sheet with ion permeability and insulation. Specific examples of porous sheets include microporous films, woven fabrics, and nonwoven fabrics. Preferred materials for the separator 13 include polyethylene, polypropylene, copolymers of ethylene and α-olefins, and cellulose. The separator 13 can be either a single-layer structure or a multilayer structure. A heat-resistant layer containing inorganic particles or a heat-resistant layer composed of resins with high heat resistance, such as aromatic polyamide resins, polyimides, and polyamide-imides, can also be formed on the surface of the separator 13.
[0054] Example
[0055] The present invention will be further illustrated below by way of examples, but the present invention is not limited to these examples.
[0056] <Example 1>
[0057] [Synthesis of ionic compound A1]
[0058] 3-Trimethoxysilylpropyl chloride and 1-methylimidazole were added to a specified reaction vessel and stirred at 95°C for 24 hours. After natural cooling, dehydrating ether was added to the reaction vessel and stirred and allowed to stand. The supernatant was then removed. This operation was repeated 4 times. The lower oil layer was dried to constant weight under high vacuum at 40°C to obtain compound A0 as shown in formula (1).
[0059] Equation (1)
[0060] Inside a glove box, compound A0, dehydrated dichloromethane, and sodium hexafluorophosphate were added to a designated reaction vessel and stirred at room temperature for 5 days. The suspension was then filtered through a membrane filter, concentrated, and dried at 40°C under high vacuum to obtain the ionic compound A1 shown in formula (2).
[0061] Equation (2)
[0062] [The production of the positive electrode]
[0063] A lithium-containing transition metal composite oxide is used as the positive electrode active material. The positive electrode active material, acetylene black, polyvinylidene fluoride, and the aforementioned ionic compound Al are mixed in a specified mass ratio, and N-methyl-2-pyrrolidone (NMP) is used as the dispersion medium to prepare a positive electrode slurry. Next, the positive electrode slurry is coated onto a positive electrode core made of aluminum foil. After drying and compressing the coating, it is cut into specified electrode sizes to obtain the positive electrode.
[0064] [Preparation of non-aqueous electrolytes]
[0065] Ethyl carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) are mixed in a specified volume ratio. LiPF6 is then added to this mixed solvent to obtain a non-aqueous electrolyte.
[0066] [Fabrication of the Experimental Battery Cell]
[0067] An electrode body is formed by arranging the positive electrode and the negative electrode (made of lithium metal foil) opposite each other through a separator. The electrode body and the non-aqueous electrolyte are housed in an outer casing made of aluminum laminate. Then, the opening of the outer casing is sealed to obtain a test battery cell (non-aqueous electrolyte secondary battery).
[0068] For the test battery cell of Example 1, the cycle characteristics (capacity retention after cycling) were evaluated using the following method (the same applies to the Examples and Comparative Examples described later). The evaluation results, along with the amount of ionic compound added, are shown in Table 1.
[0069] [Evaluation of Cyclic Characteristics]
[0070] At a temperature of 25°C, the test battery cell of Example 1 was charged with a constant current of 0.2C until the battery voltage reached 4.5V, and then charged with a constant voltage of 4.5V until the current reached 0.02C. Afterward, it was discharged with a constant current of 0.2C until the battery voltage reached 2.5V. This charge-discharge cycle was repeated 50 times.
[0071] Calculate the discharge capacity of the first cycle and the discharge capacity of the 50th cycle of the above cyclic test, and then calculate the capacity retention rate using the following formula.
[0072] Capacity retention (%) = (Discharge capacity at 50th cycle ÷ Discharge capacity at 1st cycle) × 100
[0073] <Examples 2-6>
[0074] In the fabrication of the positive electrode, the amount of ionic compound A1 added relative to the positive electrode active material was changed to the amount shown in Table 1. Otherwise, the test battery cell was fabricated in the same manner as in Example 1.
[0075] <Example 7>
[0076] The test cell was fabricated in the same manner as in Example 4, except that the ionic compound A2, which changed the counter anion from PF6 to PO2F2, was used.
[0077] <Example 8>
[0078] The test cell was fabricated in the same manner as in Example 4, except that the ionic compound A3, which changed the counter anion from PF6 to bis(fluorosulfonyl)imide (FSI), was used.
[0079] <Comparative Example 1>
[0080] In the fabrication of the positive electrode, no ionic compound A1 was added. Otherwise, the experimental battery cell was fabricated in the same manner as in Example 1.
[0081] [Table 1]
[0082] Example 1 A1 <![CDATA[PF6]]> 0.25 93.9% Example 2 A1 <![CDATA[PF6]]> 0.50 94.1% Example 3 A1 <![CDATA[PF6]]> 0.75 94.4% Example 4 A1 <![CDATA[PF6]]> 1.00 94.9% Example 5 A1 <![CDATA[PF6]]> 1.50 94.4% Example 6 A1 <![CDATA[PF6]]> 1.75 93.6% Example 7 A2 <![CDATA[PO2F2]]> 1.00 95.0% Example 8 A3 FSI 1.00 94.9% Comparative Example 1 - - - 93.5%
[0083] As shown in Table 1, the test battery cells of the embodiments exhibited higher capacity retention and superior cycle characteristics after charge-discharge cycles compared to the test battery cells of the comparative examples. In particular, the improvement in cycle characteristics was more significant when the amount of ionic compound added relative to the active material was 1.75% or less, and further 1.50% by mass or less.
[0084] Explanation of reference numerals in the attached figures
[0085] 10 Non-aqueous electrolyte secondary battery, 11 Positive electrode, 12 Negative electrode, 13 Separator, 14 Electrode body, 16 Outer casing, 17 Sealing body, 18, 19 Insulating plate, 20 Positive electrode lead, 21 Negative electrode lead, 22 Groove section, 23 Internal terminal plate, 24 Lower valve body, 25 Insulating component, 26 Upper valve body, 27 Cover, 28 Gasket, 30 Positive electrode core, 31 Positive electrode flux layer, 40 Negative electrode core, 41 Negative electrode flux layer
Claims
1. An electrode mixture comprising an active material capable of absorbing, storing, and releasing lithium for use in batteries. The electrode mixture also contains ionic compounds chemically bonded to the surface of the active material. The ionic compound contains: a binding site with the active substance, an organic cation, and a counter anion of the organic cation. The content of the ionic compound is 0.25–1.75% by mass relative to the mass of the active substance. The organic cation comprises at least one selected from the group consisting of ammonium cations, imidazolium cations, piperidinium cations, pyridinium cations, pyrrolidineium cations, morpholinium cations, sulfonium cations, and phosphonium cations. The counteracting anion includes those selected from PF6. - BF4 - N(SO2CF3)2 - N(SO2F)2 - PO2F2 - At least one of the following groups: bis(oxalato)borate anion and difluoro(oxalato)borate anion.
2. The electrode mixture according to claim 1, wherein, The bonding site is derived from hydrolyzable silane.
3. The electrode mixture according to claim 1 or 2, wherein, The silicon content is 0.03 to 0.25% by mass relative to the total mass of the active material and the ionic compound.
4. The electrode mixture according to any one of claims 1 to 3, wherein, The active material comprises a lithium-containing transition metal composite oxide.
5. The electrode mixture according to claim 4, wherein, The lithium-containing transition metal composite oxide comprises a layered rock salt-type crystal structure, consisting of the general formula LiNi x M 1-x O2 represents a composite oxide, where M is selected from at least one of the groups consisting of Al, Mn, and Co, and 0.3 ≤ x < 1.
0.
6. A non-aqueous electrolyte secondary battery, comprising: a positive electrode, a negative electrode, and a non-aqueous electrolyte. At least one of the compound layers of the positive electrode and the negative electrode is composed of the electrode compound according to any one of claims 1 to 5.
Citation Information
Patent Citations
Lithium secondary battery
JP2002319405A
Lithium iron phosphate cathode material, lithium ion battery and preparation method thereof
CN107834070A